الاختصاص القضائي بالنظر في عقد التامين الدولي - عبد الله خيري عبد الله, مرتضى (Revue jurisprudence, 2018)
قد لا يلجأ أن النصوصاع إلي تحديد المحكمة المختصة بالنزاع، وهنا يتم تحديد الاختصاص القضائي وفقا للقواعد العامة سواء الشخصية أو الموضوعية، ولكن المشرع قد خرج عن تلك القواعد فيما يتعلق بعقد التأمين . ولكن قد يقرر أطراف عقد التأمين مسألة الاختصاص بناء علي الشرط المانح للاختصاص، حيث أن النصوص غالبا ما تترك - في الواقع - لإطراف العقد حرية اختيار المحكمة المختصة وهنا يدور التساؤل عن نطاق تلك الحرية وبخاصة في مجال عقد التأمين . الكلمات المفتاحية : عقد التامين - الاختصاص الدولي - المنازعات الدولية .   Abstract: Dimensions conflict parties may resort to determine authority dispute court where the jurisdiction can be specified according to common basics whether the subjective or personal, but the legislator may be diverted away from the regulations with respect to insurance contract. On the one hand, the contract parties may decide on specialization based on the donor terms to specialization since the texts mostly left-in reality- to contract party’s selection freedom to the specialized court. Here, questions may be raised about the scope of that freedom in the field of insurance contract in particular. Keywords : Insurance contract. International Jurisdiction International Disputes .